2012
DOI: 10.1111/j.1365-4632.2012.05654.x
|View full text |Cite
|
Sign up to set email alerts
|

A review of applications of tea tree oil in dermatology

Abstract: Tea tree oil (TTO) is an essential oil, steam-distilled from the Australian native plant, Melaleuca alternifolia. It has a minimum content of terpinen-4-ol and a maximum content of 1, 8-cineole. Terpinen-4-ol is a major TTO component which exhibits strong antimicrobial and anti-inflammatory properties. Tea tree oil exerts antioxidant activity and has been reported to have broad-spectrum antimicrobial activity against bacterial, viral, fungal, and protozoal infections affecting skin and mucosa. Several studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
118
1
23

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(157 citation statements)
references
References 43 publications
2
118
1
23
Order By: Relevance
“…Hammer et al, (2006) concluded that it may be used externally in its diluted form by the majority of individuals without adverse effect (provided oxidation is avoided) [19]. Topical application of high concentrated TTO can cause adverse reactions like skin irritation, allergic contact dermatitis, systemic contact dermatitis, erythema multiform like reactions, and systemic hypersensitivity reactions [19,20]. We didn't provide any constructed information about appropriate dose which will treat infection without any kind of adverse effect.…”
Section: Limitationsmentioning
confidence: 99%
“…Hammer et al, (2006) concluded that it may be used externally in its diluted form by the majority of individuals without adverse effect (provided oxidation is avoided) [19]. Topical application of high concentrated TTO can cause adverse reactions like skin irritation, allergic contact dermatitis, systemic contact dermatitis, erythema multiform like reactions, and systemic hypersensitivity reactions [19,20]. We didn't provide any constructed information about appropriate dose which will treat infection without any kind of adverse effect.…”
Section: Limitationsmentioning
confidence: 99%
“…(Paisooksantivatana and Buain, 2009), leaves and terminal branches of Melaleuca alternifolia (Myrtales: Myrtaceae) (Pazyar et al, 2013). Terpinen-4-ol has many pharmacological activities such as anti-inflammation (Hart et al, 2000;Jeenapongsa et al, 2003), and anti-hypersensitivity (Lahlou et al, 2003).…”
Section: Terpinen-4-ol Induces Autophagic and Apoptotic Cell Death Inmentioning
confidence: 99%
“…Aunque el AAT contiene más de 100 compuestos 4 , su principal componente es el terpinen-4-ol 2,4,11,12 , al que se atribuye la mayor actividad antimicrobiana 1 . Actualmente su composición se regula por una norma internacional, que establece cantidades máximas y/o mínimas para 14 componentes del aceite (International Organization for Standarization, 1996), y define por lo menos un 30% de terpinen 4-ol y no más de un 15% de 1.8 cineol 13 .…”
Section: Discussionunclassified
“…El aceite de árbol de té (AAT) es uno de estos productos cuyo uso ha aumentado en los últimos tiempos 1 . Se trata de un aceite esencial, una mezcla compleja de hidrocarburos terpénicos y alcoholes terciarios destilada de las hojas del árbol denominado Melaleuca alternifolia [1][2][3][4] , procedente de Australia, de la familia Myrtaceae 5 , que incluye alrededor de 3000 especies 1 . Se utiliza por sus beneficios medicinales, ya que se le atribuye capacidad antisépica 6 , antifúngi-ca 7,8 y antiviral 9 .…”
Section: Servicio De Dermatología Complejo Hospitalario De Navarraunclassified